Max Uhle - Julio Tello: A political-academic controversy in the conformation of Peruvian archaeology - Ramos, Alejandra (2013)
Max Uhle (1856-1944) and Julio Tello (1880-1947) made prominent contributions to the development of Peruvian archaeology in the first half of the 20th century, coinciding at some points and differing in others. Their contrasting academic proposals were linked to political positions, which in turn impacted the way of imagining the development of Peruvian archaeology. The article analyzes how the interdependence in the characterizations of Uhle and Tello led to the formation of a mirrored logic, placing them in two poles that condense positive and negative assessments, respectively. Finally, we explore the passage from the opposition of both figures to the construction of exclusive and nationality-dependent ways of doing research.